2012
DOI: 10.1016/j.micinf.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Translocon-independent intracellular replication by Pseudomonas aeruginosa requires the ADP-ribosylation domain of ExoS

Abstract: Pseudomonas aeruginosa, a significant cause of human morbidity and mortality, uses a type 3 secretion system (T3SS) to inject effector toxins into host cells. We previously reported that P. aeruginosa uses ADP-ribosyltransferase (ADPr) activity of the T3SS effector ExoS for intracellular replication. T3SS translocon (ΔpopB)-mutants, which can export, but not translocate effectors across host membranes, retained intracellular replication. We hypothesized that secreted effectors mediate translocon-independent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…We previously reported that the ADPr domain of ExoS confers intracellular replication without the T3SS translocon or other known effectors [30]. Thus, we tested if this domain of ExoS impacts P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the ADPr domain of ExoS confers intracellular replication without the T3SS translocon or other known effectors [30]. Thus, we tested if this domain of ExoS impacts P.…”
Section: Resultsmentioning
confidence: 99%
“…Like wild-type P. aeruginosa , replication of popB mutants is dependent on the ADPr activity of ExoS [30]. …”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy suggests that intracellular P. aeruginosa remains confined in vacuoles in THP-1 cells for at least 24 h and can actively replicate therein. A vacuolar localization of P. aeruginosa has also been generally observed in epithelial cells (7,13,33), but the nature of the infected vacuoles has not yet been determined (31).…”
Section: Discussionmentioning
confidence: 99%
“…This is important for P. aeruginosa because it produces a variety of virulence factors that can affect host cell viability. In strain PAO1, pili, flagella, a type III secretion system, exotoxin A, and lipopolysaccharide are all known to contribute to virulence (30,31). Because the expression of these factors is variable between strains and critically depends on their growth status, preliminary investigations such as those performed here will probably be necessary when expanding the model to other laboratory or clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…Our research has shown that clinical and laboratory isolates of P. aeruginosa can be divided into invasive or cytotoxic strains based upon how they interact with host cells (7). Invasive strains can survive and replicate inside epithelial cells dependent on the type III secretion system (T3SS) effector ExoS (8)(9)(10), while cytotoxic strains instead encode ExoU, which can induce rapid death of intoxicated host cells (11,12). While details of how invasive and cytotoxic strains impact host cells vary, both types can cause human disease, and they can each be virulent in animal models of infection (13)(14)(15).…”
mentioning
confidence: 99%